Dental Caries - Diagnosis, Prevention and Management 2018
DOI: 10.5772/intechopen.76300
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Caries Update

Abstract: Early childhood caries (ECC) is the most common chronic disease among young children who are less than 71 months of age and is currently represented as a public health problem in various countries worldwide. Dental caries continues to be a major health problem in developing nations because of lack of education, awareness, and poor socioeconomic status. It begins with white-spot lesions on upper primary incisors along the margin of the gingiva and leads to complete destruction of the crown. The potential impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The study’s results underscore the crucial role of maintaining proper oral hygiene and reducing sugary food and drink intake as cornerstones of preventing dental caries in children. This aligns with the recommendations from the American Academy of Pediatric Dentistry, which emphasizes the importance of establishing a dental home and regular check-ups as part of effective early preventive care ( Edem, 2018 ). Incorporating subjective data could enhance our understanding of behavioral and psychosocial elements that contribute to dental health.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The study’s results underscore the crucial role of maintaining proper oral hygiene and reducing sugary food and drink intake as cornerstones of preventing dental caries in children. This aligns with the recommendations from the American Academy of Pediatric Dentistry, which emphasizes the importance of establishing a dental home and regular check-ups as part of effective early preventive care ( Edem, 2018 ). Incorporating subjective data could enhance our understanding of behavioral and psychosocial elements that contribute to dental health.…”
Section: Discussionsupporting
confidence: 72%
“…The importance of dental health, particularly in children, cannot be overstated. It is a critical aspect of overall health and well-being, influencing not just the condition of the mouth but also impacting general health, nutrition, and quality of life ( Edem, 2018 ; Sadegh-Zadeh et al, 2022 ). Dental health issues, particularly dental caries, remain one of the most common chronic diseases of childhood, recognized globally as a significant public health challenge ( World Health Organization, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosing and assessing ECC in children with autism and developmental disorders requires sensitivity, patience, and tailored approaches to accommodate their unique needs and challenges. Early detection of ECC is crucial for preventing complications, preserving primary teeth, and promoting long-term oral health and well-being (Edem, 2018). Collaboration between dental professionals, caregivers, and healthcare providers is essential to ensure timely diagnosis and effective management of ECC in this vulnerable population…”
Section: Importance Of Early Detectionmentioning
confidence: 99%
“…Previous research studies on dental caries were mostly based on a dental evaluation corresponding with DMFT that showed the number of decayed, missing, filled teeth which was used to analyze the caries involvement and prevention of primary and permanent molar teeth with regard to ICDAS score. [ 5 ] These previous research articles have also shown that there was high-risk incidence of restorations that were mainly due to lack of awareness on various aspects and fields of class I caries in many counties. These previous articles have shown that the prevalence of caries includes low socioeconomic status and lack of availability in dentistry.…”
Section: Introductionmentioning
confidence: 99%